The family in cross - cultural perspective - Stephens, William (New York: Holt, Rinehart and Winston, Inc, 1963)
Contents : Marriage defined,the family defined,plural marriage,kinship,mate choice,marriage,and divorce,sex restrictions,roles of husband and wife,power and deference,child rearing,cross-cultural regularities.
Icludes bibliographical references and index
Keywords: Familia - Sociología Familiar